Clinical Advances in Chronic Intestinal Diseases Treatment - Mesonero, Jose E.; Latorre, Eva (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Chronic intestinal diseases are increasing around the world. With poor quality of life and expensive healthcare costs, the patients demand novel approaches and treatments for better clinical outcomes. This book illustrates the state of the art and the envisaged near future in the management of these pathologies.